Inhibition of Excessive Oxidative Protein Folding Is Protective in MPP+ Toxicity-Induced Parkinson's Disease Models - Lehtonen Šárka; Jaronen Merja; Vehviläinen Piia; Lakso Merja; Rudgalvyte Martina; Keksa-Goldsteine Velta; Wong Garry; Courtney Michael J.; Koistinaho Jari; Goldsteins Gundars (MARY ANN LIEBERT, INC, 2022)
Aims: Protein misfolding occurs in neurodegenerative diseases, including Parkinson's disease (PD). In endoplasmic reticulum (ER), an overload of misfolded proteins, particularly alpha-synuclein (alpha Syn) in PD, may cause stress and activate the unfolded protein response (UPR). This UPR includes activation of chaperones, such as protein disulphide isomerase (PDI), which assists refolding and contributes to removal of unfolded proteins. Although up-regulation of PDI is considered a protective response, its activation is coupled with increased activity of ER oxidoreductin 1 (Ero1), producing harmful hydroperoxide. The objective of this study was to assess whether inhibition of excessive oxidative folding protects against neuronal death in well-established 1-methyl-4-phenylpyridinium (MPP+) models of PD. Results: We found that the MPP+ neurotoxicity and accumulation of aSyn in the ER are prevented by inhibition of PDI or Ero1 alpha. The MPP+ neurotoxicity was associated with a reductive shift in the ER, an increase in the reduced form of PDI, an increase in intracellular Ca2+, and an increase in Ca2+-sensitive calpain activity. All these MPP+-induced changes were abolished by inhibiting PDI. Importantly, inhibition of PDI resulted in increased autophagy, and it prevented MPP+-induced death of dopaminergic neurons in Caenorhabditis elegans. Innovation and Conclusion: Our data indicate that although inhibition of PDI suppresses excessive protein folding and ER stress, it induces clearance of aggregated aSyn by autophagy as an alternative degradation pathway. These findings suggest a novel model explaining the contribution of ER dysfunction to MPP+-induced neurodegeneration and highlight PDI inhibitors as potential treatment in diseases involving protein misfolding.